КОСТЮМБОП ТЎҚИМАЛАРДА ИП БУРАМЛАРИНИНГ ҲАВО ЎТКАЗУВЧАНЛИГИГА ТАЪСИРИ - Оразбаева, Р.И.; Қодирова, Д.Н.; Раҳимхўжаев, С.С.; Турениязова, Л.А. (SCIENCE and SOCIETY, 2021)
As a criterion for assessing the structure of clothing fabrics, it is advisable to use air permeability. Therefore, it is proposed, on the basis of an experimental tissue sample, to assess the parameters of a tissue with a square structure. A technique for analyzing an experimental tissue sample has been developed. Where the following parameters of a fabric with a square structure of a plain weave are determined, such as the relative density of the fabric, the percentage of uncovered area of the fabric, the coefficient of air permeability, the indicator of the degree of pressure and air permeability. The parameters of the square fabric parameters are obtained depending on the yarn twist coefficient in the metric system. As the yarn twist factor in the metric system increases, the percentage of uncovered fabric area, the air permeability coefficient and the air permeability of the square fabric increase, and the relative density of the fabric and the degree of pressure decrease.